Analysis of product mix, capacity release, and utilities - García Vidal, Gelmar (2021)
The objective of the article is to present the design and application of a technique based on the Cost - Volume - Benefit method, in order to have economic - financial information of the right mix of products that allows achieving the expected results of the organization in a negotiation process. The proposed analysis has the usual components of the Cost - Volume - Benefit method, namely unit price, unit variable cost, operating expenses and financial expenses. The technique consists of ten steps that will lead to create as many scenarios as necessary in which the mix of products, the installed capacity and the profits of the organization will be evaluated, the ultimate goal of the same. These steps, through the formulations that allow their application, will explain the way to achieve the desired profits or the point of balance with a certain composition of products. The application is made in a small business consisting of a machining workshop. The results obtained show that the proposed technique allows the achievement of the stated objective, in the case that occupies a level of desired utilities. This research provides an economic-financial perspective so that entrepreneurs have the information required to prepare the negotiation processes and can make the most pertinent decisions in order to achieve the expected results.